2014
DOI: 10.1021/ol500505k
|View full text |Cite
|
Sign up to set email alerts
|

Fe-Catalyzed Novel Domino Isomerization/Cyclodehydration of Substituted 2-[(Indoline-3-ylidene)(methyl)]benzaldehyde Derivatives: An Efficient Approach toward Benzo[b]carbazole Derivatives

Abstract: A new and efficient protocol to synthesize substituted benzo[b]carbazole derivatives has been demonstrated involving iron-catalyzed domino isomerization/cyclodehydration sequences from substituted 2-[(indoline-3-ylidene)(methyl)]benzaldehyde derivatives. The substrates could be easily made via Pd-catalyzed domino Heck-Suzuki coupling from 2-bromo-N-propargylanilide derivatives in high yields. Notably, the generality and efficiency of this two-stage domino strategy was further exemplified by the synthesis of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…1636 This transformation was achieved in the presence of iron(III) chloride as catalyst in 1,2-dichloroethane at …”
Section: Domino Reactionsmentioning
confidence: 99%
“…1636 This transformation was achieved in the presence of iron(III) chloride as catalyst in 1,2-dichloroethane at …”
Section: Domino Reactionsmentioning
confidence: 99%
“…[8] The exo-dig cyclization was also possible giving the fused five-membered heterocycle (Scheme 1, b). [9] In the metal-free hydroarylation reaction, the carbon-carbon bond of alkyne is activated by using an electrophilic source, such as halogen, organoselenium compounds or hypervalent iodine reagent among others, forming a halonium (selenonium) ion intermediate. The attack of the electron cloud from the aromatic ring at the activated triple bond produces the stabilized carbocation I.…”
Section: Introductionmentioning
confidence: 99%
“…The hydroarylation processes join the carbon nucleophilic of the aryl moiety with more external active carbon of the alkyne in an endo ‐dig mode (Scheme , a) . The exo ‐dig cyclization was also possible giving the fused five‐membered heterocycle (Scheme , b) . In the metal‐free hydroarylation reaction, the carbon‐carbon bond of alkyne is activated by using an electrophilic source, such as halogen, organoselenium compounds or hypervalent iodine reagent among others, forming a halonium (selenonium) ion intermediate.…”
Section: Introductionmentioning
confidence: 99%
“…However, literature search reveals that, although plenty of methods are available for the synthesis of various indole derivatives by means of palladium‐catalyzed reactions from aniline derivatives,3d,14 no selective method has been developed for the synthesis of C‐3‐substituted indole derivatives. During our recent study on the synthesis of benzo[ b ]carbazole derivatives,13f we observed that these reaction conditions did not work for substituted 3‐methyleneindoline derivatives. So, we decided to perform a thorough investigation of this transformation.…”
Section: Introductionmentioning
confidence: 99%